2009
DOI: 10.1002/pbc.21935
|View full text |Cite
|
Sign up to set email alerts
|

Objective response of multiply recurrent low‐grade gliomas to bevacizumab and irinotecan

Abstract: Multiply recurrent low-grade gliomas in children are responsive to the combination of bevacizumab and irinotecan. The drug combination has been relatively well tolerated, including in patients with neurofibromatosis type 1, and warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 20 publications
9
110
0
Order By: Relevance
“…16 Several studies have also indicated that VEGF and VEGFR antagonists have roles in the treatments of other brain tumors, including vestibular schwannomas, meningiomas, and low-grade astrocytomas. 5,[7][8][9]11,12,17,18 Despite being nonmalignant brain tumors, vestibular schwannomas and meningiomas carry significant morbidity and risk of mortality for certain patients. Many but not all of these tumors can be treated with surgery or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several studies have also indicated that VEGF and VEGFR antagonists have roles in the treatments of other brain tumors, including vestibular schwannomas, meningiomas, and low-grade astrocytomas. 5,[7][8][9]11,12,17,18 Despite being nonmalignant brain tumors, vestibular schwannomas and meningiomas carry significant morbidity and risk of mortality for certain patients. Many but not all of these tumors can be treated with surgery or radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The fivedrug University of California at San Francisco (UCSF) regimen (6-thioguanine, procarbazine, dibromodulcitol, lomustine, and vincristine) has been reported to be similarly efficacious; a randomized trial comparing carboplatin-vincristine to this regimen has been completed in COG, suggesting equal or greater efficacy with the five-drug regimen (13). Bevacizumab in combination with irinotecan has been investigated for recurrent LGA with promising response rates for heavily pretreated patients (16). The decision to proceed with CT or RT relates to patient age and clinical presentation; factors beyond age alone include symptoms and signs, potential for additional neurocognitive deficits, the likelihood of durable benefit from respective chemotherapeutic regimens, and the radiation volume required in weighing relative potential toxicities.…”
Section: Chemotherapymentioning
confidence: 99%
“…Multiple chemotherapeutic agents have been shown to delay progression (210,212). The most commonly administered regimen is the combination of carboplatin and vincristine.…”
Section: Chemotherapymentioning
confidence: 99%
“…In a recent phase I study of Lenalidomide (an immune modulating drug and angiogenesis inhibitor) in children with recurrent brain tumors, Warren et al, reported objective responses in 2 patients with an optic pathway glioma and pilocytic astrocytoma respectively (Warren, Goldman et al 2011). Similarly, Packer et al, have observed sustained objective responses or disease stabilization and improvement in neurologic deficits in 7 of 9 children with multiply recurrent LGG treated with Bevacizumab plus irinotecan (Camptosar™, Pfizer corporation, USA) (Packer, Jakacki et al 2009). A multi-institutional phase II trial of the same combination in children with recurrent LGG has just been completed and results of this study should be available soon.…”
Section: Molecular Alterations In Pediatric Lgg and Novel Therapiesmentioning
confidence: 99%